Beneficial effects of a pyrroloquinolinequinone-containing dietary formulation on motor deficiency, cognitive decline and mitochondrial dysfunction in a mouse model of Alzheimer's disease. Issue 4 (April 2017) - Sawmiller, Darrell; Li, Song; Mori, Takashi; Habib, Ahsan; Rongo, David; Delic, Vedad; Bradshaw, Patrick C.; Shytle, R. Douglas; Sanberg, Cyndy; Bickford, Paula; Tan, Jun
Abstract: Alzheimer's disease (AD), a progressive neurodegenerative disorder, is linked to oxidative stress, altered amyloid precursor protein (APP) proteolysis, tau hyperphosphorylation and the accumulation of amyloid-β (Aβ) plaques and neurofibrillary tangles (NFT). A growing body of evidence suggests that mitochondrial dysfunction can be a key promoter of all of these pathologies and predicts that restoration of mitochondrial function might be a potential therapeutic strategy for AD. Therefore, in the present study, we tested the beneficial effect of a nutraceutical formulation Nutrastem II (Nutra II), containing NT020 (a mitochondrial restorative and antioxidant proprietary formulation) and pyrroloquinolinequinone (PQQ, a stimulator of mitochondria biogenesis) in 5XFAD transgenic mice. Animals were fed Nutra II for 12 weeks, starting at 3 months of age, after which behavioral and neuropathological endpoints were determined. The data from behavioral test batteries clearly revealed that dietary supplementation of Nutra II effectively ameliorated the motor deficiency and cognitive impairment of 5XFAD mice. In addition, Nutra II also protected mitochondrial function in 5XFAD mice brain, as evidenced by declined ROS levels and membrane hyperpolarization, together with elevated ATP levels and respiratory states. Interestingly, while Nutra II treatment only slightly reduced soluble Aβ42 levels, this formulation significantly impacted tau metabolism, as shown by reduced total and phosphorylated tau levels of 5XFAD mouse brain. Taken together, these preclinical findings confirm that mitochondrial function may be a key treatment target for AD and that Nutra II should be further investigated as a potential candidate for AD therapy.